Existence of solutions and error bound for vector variational inequalities in Banach spaces. (2nd September 2018) - Yao, Jen-Chih; Zheng, Xi Yin
Abstract: Without monotonicity and convexity assumptions, we provide the existence results of solutions for weak vector variational inequalities and vector variational inequalities under some kinds of continuity assumptions. We give a gap function for a weak vector variational inequality and present a sufficient condition to guarantee that the vector variational inequality has error bound property with respect to such a gap function.